Driver and inhibitor of organic food adoption: A study on Indonesian consumers / Whony Rofianto - Rofianto, Whony (UiTM Cawangan Johor, 2019)
This study aims to empirically examine the role of health consciousness and environmental concern as a driver of attitudes towards organic food. In addition, this study also tries to empirically test the positive influence of attitudes toward organic food on the intention to buy together with perceived price and perceived availability. The study was conducted through a descriptive research design based on the cross-sectional data, collected from consumer samples in Indonesia. The sample was selected using a convenience sampling technique. Data is collected through online surveys. Data analysis and hypothesis testing are carried out quantitatively using the Structural Equation Model (SEM) approach. In general, health consciousness, environmental concern, perceived prices, and perceived availability are proved as driving factors of intention to buy in the context of organic food on Indonesian consumers.